Title Vads Collection: Constance Howard Resource and Research Centre in Textiles: Material Collection - Object Name: quilted & embroidered square, square
Brief Physical Description: A square of quilted and embroidered fabric, the ground colour brown. Varying coloured bands of geometric embroidery work outwards from a square abstract central motif. Select this link for more description information.